Simulating farm structural change dynamics in Thessaly (Greece) using a recursive programming model - Mantziaris, Stamatis; Rozakis, Stelios; Karanikolas, Pavlos; Petsakos, Athanasios; Tsiboukas, Konstantinos (Firenze University Press, 2024)
Although the policy impacts on farms accumulate year by year, most farm decision models focus on short-term decisions, evaluating policies based on snapshots. Structural changes are gradually built; therefore, farm decision models should consider the sequences within the period under study. Multiyear data from the arable sector in Thessaly, Greece, have fed a newly developed recursive programming model mainly to simulate farm structural change dynamics. The proposed model incorporates new evidence on the strategic decision of arable crop farms regarding their remaining in the production system and farm expansion. Results reveal an evident gradual farmland concentration in relatively large farms, accompanied by a gradual expansion of the most profitable cropping activities, verifying the real-world survival strategy of farms.